IMPROVING THE METHODOLOGY OF MORAL EDUCATION OF SMALL GROUP EDUCATORS OF PRESCHOOL EDUCATION ORGANIZATION ON THE BASE OF NATIONAL VALUES IN THE FAMILY - Jabborova Saodat Zoirovna (Galaxy International Interdisciplinary Research Journal, 2024)
The methodology of moral education for small group educators in preschool education organizations plays a vital role in shaping children’s ethical development. Grounded in national values and family ethics, this methodology encompasses various strategies, including integrating cultural elements into the curriculum, promoting positive role models, fostering moral reflection and discussion, encouraging family involvement, and cultivating empathy and respect. Case studies illustrate the implementation of these strategies in preschool settings, highlighting the importance of storytelling, community service projects, and role-model visits. Despite challenges such as cultural diversity and time constraints, preschool educators can overcome obstacles by adopting a culturally responsive approach and fostering collaboration with families and communities. By enhancing the methodology of moral education, preschools create a nurturing learning environment where children develop empathy, respect, and a strong sense of moral responsibility, laying the foundation for a more compassionate and equitable society.